Acompanhamento operacional e avaliação de uma ECTE composta por Reator UASB – FAS no município de Uru - SP - Ribeiro, Jaqueline Cardoso [UNESP] (2015)
This research is being developed in partnership with the Basic Sanitation Company of the State of São Paulo (BSCSS) and focuses on assisting in the operational monitoring of an Effluent Treatment Station Compact (ETSC) composed of Reactor type Upflow Anaerobic Sludge Blanket (UASB) followed by Submerged Aerated Filter (SAF), located in the municipality of Uru-SP. This monitoring is being done through physical-chemical analyzes that have 24 weeks of duration prediction through weekly collections of each stage of the treatment and monthly collections of sludge profile from UASB reactor, such analyzes aim to evaluate treatment efficiency in each unit and the system as a whole and give guidelines for establishing the optimum operating practices to obtain a better quality effluent. It is expected that by such monitoring is possible to estimate guidelines for the volume and intervals of sludge disposal since there is a history of problems in respect of Sedimentable Solids (SS) in the station. Once the research is still in progress, so far the system has proved very effective especially in relation to removal of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) with average values above the usual for this type of treatment of at least 91% and 85% respectively. Also it is believed that monitoring has contributed to a general improvement of the system, because during the monitoring the ETSC’s (OL) Operating License was obtained which until then was being operated with an (OLPT) Operation License to Precarious Title.